PERANCANGAN DAN ANALISA CIRCULAR POLARITY ANTENNA CROSSHAIR WAVEGUIDE SEBAGAI PENGUAT WIFI ADAPTER TP-LINK TL-WN723N PADA FREKUENSI 2,4 GHZ - ., Yulianus Sandi (Faculty of Engineering, Universitas Tanjungpura, 2016)
Abstrak - Waveguide Crosshair Antenna with reflectors which has the function to change the radiation pattern and beam width antenna beam so that in itself could increase the antenna gain. The amount of change in the gain generated by the addition of the reflector can be affected by several things, among them is to set the size of the reflector panel angle (α), adjust the amount of spacing between the driven element and reflector panel (space), and change the length dimension of the reflector (h). The resulting radiation pattern waveguide Crosshair antenna is directional, the signal emitted in two directions with the same magnitude. With the addition of reflectors, will limit the radiation pattern from being widened backward and transmits force will be strengthened in the opposite direction, so that one can clearly see how it changes the transmit antenna patterns before and after the addition of the reflector, the antenna amplifier is more devoted to the working frequency of 2.4 GHz for wireless LAN ( local area network ). The parameters that must be considered in designing antennas for wireless LAN is working frequency. To test the speed of the download (download) and upload (upload), conducted through speedtest.net on two different networks, namely network UNTAN hotspot network in the faculty of engineering with download speeds of 72.23 Mbps, 50.56 Mbps upload network and the Faculty of Engineering at the speed 3.05 Mbps download, upload 2.13 Mbps, which is influenced by the speed speedtest maximum value and minimum speed provided by the ISP (internet Service Provider). Kata kunci: Crosshair Waveguide Antenna, External Antenna, Wifi Adapter frekuensi 2.4 GHz